THE EFFECT OF MENTHA PIPERIT A (L.) EXTRACT MIXED DIET ON PLASMA TOTAL PROTEIN FRACTIONS AND DISEASE RESISTANCE AGAINST EDWARDSIELLA TARDA IN ROHU (LABEO ROHITA HAM.) FINGERLINGS - Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2007)
Rohu fingerlings (Labeo rohita Ham.) were randomly divided into four groups. The control group was fed on normal diet and three treated groups namely T1, T2 and T3 groups were fed on plant Mentha piperita (L.) extract mixed diet with varying doses viz. 10, 20 and 30 mill/100 g feed, separately. After three weeks of feeding, blood was collected from all the groups for testing of plasma total protein, albumin (A), globulin (G) levels and AIG ratio. Then, all the fish groups were immunized intraperitoneally (i.p.) with 1% formalin-killed E. tarda suspension (106 cells/fish). The laboratory analysis was done weekly after immunization. Then all the groups were challenged (i.p) with live E. tarda suspension for testing of disease resistance against the bacteria. The results indicated that plasma total protein and globulin levels significantly (P < 0.05) increased in the plant extract treated groups compared to that in the control group. After immunization and one week of challenge, the plasma total protein and globulin levels significantly ( P < 0.05) increased in both the control and treated groups. However, there was no significant (P > 0.05) difference in AIG ratio among groups during the experiments. The plant extract mixed diet enhanced disease resistance against E. tarda infection in the plant extract treated fish.